Optimizing Sliding Mode Controller in a DC Microgrid with Variant Constant Power Loads - Al-Modaffer, Ameen M.; Chlaihawi ِAmer A.; Shabeeb, Dhulfiqar M. (Engineering, Technology & Applied Science Research, 2024)
The optimization of a suitable controlling method is a priority in running any DC/DC boost converter effectively. However, a problem may arise as the occurring oscillations in the microgrid caused by the incremental negative resistance of the Constant Power Poad (CPL) variation may lead to system instability. In order to tackle this intrinsic problem, three proposed Sliding Mode Control (SMC) methods were simulated and examined against multiple variations of CPL in MatLab/Simulink. Integral Sliding Mode Control (ISMC) and Two-variable Sliding Mode Control (TSMC) methods showed a better system performance than the Low Pass Filter SMC (LPFSMC) in terms of stability of output voltage in both steady state and transient conditions. The output voltages of ISMC and TSMC had a margin of error of approximately 1 V in the steady-state response and a minor overshoot of less than 1% in the transient response. The steady-state output voltage when using LPFSMC showed approximately 3 V of error and the transient state had a noticeable overshoot near 3%. However, all three controlling methods had a similar efficiency of around 98%. The outstanding robustness of ISMC exhibited the highest voltage stability with the lowest chattering in both steady state and transient responses through the compensation of adequate current to satisfy the CPL requirement.